Truck front underrun protection parameter and identification - Jävert, Herman; Müller, John (My University, 2026)
Frontal collisions between heavy goods vehicles and passenger cars remain a major traffic safety challenge due to differences in mass, stiffness, and structural geometry. Although FUP systems are intended to improve structural interaction and reduce underride risk, limited information is available regarding how modern heavy goods vehicles front structures geometrically interact with passenger car load paths. This thesis investigates geometric parameters of modern European heavy goods vehicles front structures with focus on frontal crash compatibility with passenger cars. A Truck Front Component Measurement database was established from collected vehicle measurements and compared with passenger car structural data and historical truck data from the VC-Compat project. The analysis considered vertical, transverse, and longitudinal positioning of selected frontal structural components and simplified overlap configurations. The result indicate that alignment between truck frontal structures and passenger car load-carrying components is limited in several investigated configurations, particularly when overlap is reduced. The findings suggest that geometric compatibility should be considered together with strength and deformation requirements when evaluating FUP performance. However, the study is based on simplified geometric analysis and publicly available or manually collected data, and therefore does not provide a complete assessment of crash performance. Further work involving validated simulations or physical testing is required to assess the dynamic effects of the identified parameters.
Keywords: crashworthiness, structures, heavy goods vehicles, compatibility